2003
DOI: 10.1007/s00464-002-9162-6
|View full text |Cite
|
Sign up to set email alerts
|

Matched-pair comparison of three different approaches for thymectomy in myasthenia gravis

Abstract: There was adequate cumulative medium-term improvement of MG and less postoperative morbidity after tThx, which may become the preferred technique for Thx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Two studies were eligible to compare different extents of thymic resection via median sternotomy, including 175 participants. 39,40 Figure 2 shows that the risk of achieving CSR at 3 years of follow-up was similar in patients who underwent extended transsternal compared to those who underwent basic transsternal thymectomy (RR 1.48, 95% CI 0.36–6.08, I 2 = 80%, p = 0.58; data available on Dryad, figures e-1–e-3, doi.org/10.5061/dryad.k98sf7m4w). Note, however, that the CIs for this analysis were quite wide given the low number.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Two studies were eligible to compare different extents of thymic resection via median sternotomy, including 175 participants. 39,40 Figure 2 shows that the risk of achieving CSR at 3 years of follow-up was similar in patients who underwent extended transsternal compared to those who underwent basic transsternal thymectomy (RR 1.48, 95% CI 0.36–6.08, I 2 = 80%, p = 0.58; data available on Dryad, figures e-1–e-3, doi.org/10.5061/dryad.k98sf7m4w). Note, however, that the CIs for this analysis were quite wide given the low number.…”
Section: Resultsmentioning
confidence: 98%
“…A total of 1,598 patients with MG were enrolled in the 12 cohort studies and 1 randomized clinical trial included (figure 1). From the cohort studies, 7 involved 889 patients without thymoma, 39-44 4 studies involved 431 patients with or without thymoma, 12,45-47 and 1 study included 187 patients with thymoma. The 1 randomized study included only patients without thymoma.…”
Section: Resultsmentioning
confidence: 99%
“…Both TT for myasthenia gravis and TS for hyperhidrosis have been proved as effective treatments. [1389]…”
Section: Discussionmentioning
confidence: 99%
“…[2] In recent years, thoracoscopic thymectomy (TT) has been described as being able to achieve the same functional improvement as median sternotomy or the transcervical approach, but with less morbidity. [3]…”
Section: Introductionmentioning
confidence: 99%
“…Although total thymectomy is considered the goal of surgery, it has not been clearly shown that this is necessary, nor is it certain that all the surgical techniques are able to achieve this goal [4]. Although transsternal thymectomy has been the standard approach for many years, other options have been reported [5][6][7][8][9][10]. Nevertheless, the optimal surgical approach to thymectomy is still a matter of debate.…”
Section: Introductionmentioning
confidence: 97%